1996
DOI: 10.1007/bf00173273
|View full text |Cite
|
Sign up to set email alerts
|

Presettlement analogs for Quaternary fire regimes in eastern North America

Abstract: We present a method for identifying analogs for past fire regimes and use it to assess similarity between late Quaternary fire regimes in northern Wisconsin and central New York and a reference set of charcoal series from just prior to presettlement time. The analog method is based on comparisons of distributions of charcoal accumulation rates from annually laminated sediments using a Kolmogorov-Smirnov two-sample D statistic (D). D is a nonparametric statistic expressing the difference between distributions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…To compare presettlement charcoal accumulation between the two regions, we examined the distributions of charcoal accumulation rates from 1000 to 1850 AD using a non‐parametric Kolmogorov‐Smirnov (KS) two‐sample test [ Sokal and Rohlf , 1981; Clark et al , 1996a]. Charcoal records contain information on regional fire importance, although charcoal accumulation rates may vary between sediment types [ Clark et al , 1996d].…”
Section: Field and Laboratory Methodsmentioning
confidence: 99%
“…To compare presettlement charcoal accumulation between the two regions, we examined the distributions of charcoal accumulation rates from 1000 to 1850 AD using a non‐parametric Kolmogorov‐Smirnov (KS) two‐sample test [ Sokal and Rohlf , 1981; Clark et al , 1996a]. Charcoal records contain information on regional fire importance, although charcoal accumulation rates may vary between sediment types [ Clark et al , 1996d].…”
Section: Field and Laboratory Methodsmentioning
confidence: 99%
“…However, sites with sandier, excessively drained soils showed a slight increase in fire frequencies and were associated with rapid pollen assemblage shifts over a few decades and compositional volatility. Disturbance and vegetation feedbacks on fire can either facilitate shifts in species composition (Davis and Botkin 1985, Overpeck et al 1990, Bradshaw and Hannon 1992, Clark et al 1996, Clark et al 2001, Scheller and Mladenoff 2005, Booth et al 2012 or maintain stability of vegetation types during climate changes (Heinselman 1973, Cleland et al 2004, Lytle 2005, Umbanhowar et al 2006. Overall, change in vegetation composition on the NWSP during the LIA was driven by variation in soils and local climate more than by changing fire frequencies.…”
Section: Patterns Of Variation In Species Compositionmentioning
confidence: 99%
“…In the extreme northern boreal forest, it has been suggested that fire has triggered landscape fragmentation over several millennia, without any change in the location of the northern tree‐line (Payette & Lavoie 1994). Changes in flammability may explain the occurrence of different fire regimes through time, both in conifer and broad‐leaved forests (Clark 1988; Clark et al . 1996a,b).…”
Section: Introductionmentioning
confidence: 99%
“…1996a,b). Vegetation and fire change almost in synchrony (Clark et al . 1996a), and either could be the driving force.…”
Section: Introductionmentioning
confidence: 99%